PENGARUH POSISI MENERAN TERHADAP RUPTURE PERENIUM PADA PERSALINAN NORMAL DI PMB NY "I" SINGOSARI KABUPATEN MALANG - Anil Masyayih, Warda; Siswati, Eny; Rina Mardiana, Heppy; Hidayati, Nurul (PRIMA WIYATA HEALTH, 2023)
The pressing position at the time of delivery greatly affects the occurrence of tears in the birth canal (perineal rupture), especially in primiparas, but can also occur in multiparas and can even occur in grande multi. The pushing position is a comfortable position for mothers in labor. Mothers can change positions regularly during the second stage of labor, as this often speeds up the progress of labor and mothers may be able to push effectively in certain positions that are considered comfortable for the mother.The research design used is correlational analytic research. The cross sectional design is a research design by measuring or observing at the same time (one time). All mothers gave birth in PMB Ny "I" Singosari Malang Regency as many as 30 people using a non-probability technique: Accidental sampling. The measuring instrument used is an observation sheet, the results of which are analyzed using the Chi-square test with a significant level of 5% (α = 0.05).From the results of this study, it is known from 15 respondents with a supine position and experienced perineal rupture as many as 15 respondents (50%). Respondents with a left tilted position and experienced a rupture were 1 respondent (3.4%). Meanwhile, from the Chi-square test, the sig value is obtained. (2-tailed) or value 0.001 (because value < 0.05) then H0 is rejected and H1 is accepted.There is an Influence of Pushing Position on Perineal Rupture in Primigravida Normal Delivery In PMB Ny "I" Singosari Malang Regency, pressing position will affect the occurrence of rupture, pushing should be done if there is adequate his. The benefits of research are doing the right position during childbirth and can reduce the incidence of rupture in childbirth.